Elevated accumulation and distinct migration patterns of neonicotinoids compared to traditional insecticides in South China typical orchard - Shiming Song; Xu Li; Fenghua Wei; Jiye Zhang; Henglin Zhang; Haibao Huang; Yuankai Guo; Tao Zhang (Emerging Contaminants)
The global insecticide market is undergoing significant changes, witnessing a surge in neonicotinoids (NEOs) usage, alongside the persistent application of traditional insecticides, such as organophosphates (OPs), carbamates (CMs) and pyrethroids (PYRs). In this study, therefore, NEOs, OPs, PYRs and CMs were measured in various pomelo tissues and paired soil and leaf samples collected from two pomelo orchards in South China. NEOs exhibited a higher median sum residue in pulp (ΣNEOs: 1.90 ng/g) than traditional insecticides (ΣOPs: 1.69 ng/g, ΣCMs: 0.49 ng/g, and ΣPYRs: 0.33 ng/g). Principal component analysis indicated that NEO residues in pulp was primarily originated from deep soil. Moreover, the migration pathway of NEOs potentially extends from the deep soil to the plant's root system, then travels through the carpopodium to access the pulp, whereas traditional insecticides adhere to a migration pathway that progresses from the epicarp to the pulp. Tissue-specific distribution analysis revealed that NEOs exhibit an enhanced propensity for accumulation in the pulp. In contrast, traditional insecticides display a preference for accumulating in seeds and endocarp. This study first to delineate distinction in residue, migration, tissue-specific distribution between NEOs and traditional insecticides, heightened emphasis is warranted on NEOs and their metabolites within the ambit of the “One-Health” framework.